THE EFFECT OF LIQUIDITY, ASSET STRUCTURE AND PROFITABILITY ON DEBT POLICIES OF TRADING COMPANIES LISTED ON THE IDX 2016-2019 - Wikan Budi Utami; Suprihati Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of Liquidity, Asset Structure and Profitability on Debt Policy in trading companies listed on the Indonesia Stock Exchange in 2016-2019. The sample used in this study were 12 trading companies. The sampling method used was done by using purposive sampling. The data in this study are quantitative data. The analytical method used is multiple linear regression models. To test the hypothesis simultaneously and partially, the F test, t test and determination test (R2) were used. The results of this research hypothesis testing indicate that simultaneously the liquidity, asset structure and profitability variables simultaneously influence debt policy. Asset structure and liquidity variables affect debt policy. Meanwhile, partially the profitability variable has no effect on debt policy. The amount of determination test (Adjusted R Square) of 0.523 means that the independent variables (liquidity, asset structure and profitability) can explain the dependent variable (debt policy) by 52.3%, while the remaining 47.7% is explained by other variables outside the research model.